Ultra Low Cost, Explosiveness Test - Galante, Erick; Mai, Nathalie; Ladyman, Melissa K.; Gill, Philip P.; Temple, Tracey (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.To investigate the emissions from open burning of explosives we have burnt explosives (10 mg) in a sealed glass vial (10 cm3). As the reaction occurred inside the glass vial, it could be captured on high speed camera allowing the observation combustion reaction. The profile of gaseous emissions was later determined via Gas Chromatography Mass Spectrometry. The glass vials were placed into an aluminium block, which was heated with a gas flame until combustion was achieved. On average the heating cycle took 3-4 minutes before ignition of the explosive was observed.Interestingly, the combustion of 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) was very different to that observed for 3-Nitro-1,2,4-triazol-5-one (NTO) and 2,4-dinitroanisole (DNAN). RDX did not burn when heated as observed with NTO and DNAN. We observed that the RDX partly sublimed and then partly thermally decomposed in the gaseous phase. Then the partially decomposed RDX vapour underwent a violent burning reaction. This burn to violent reaction occurred in the gaseous phase at temperatures as low as 270 ºC.Ultimately, we understand that a similar setup could be used for assessing sensitiveness and safety aspects of new explosives formulations.
Keywords: 'RDX'; 'Slow heating'; 'Headspace vial'; 'DSDS17'; 'DSDS17 poster'; 'Organic Chemistry not elsewhere classified'; 'Analytical Spectrometry'